2020
DOI: 10.1111/jtxs.12553
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of liquid‐core hydrogel beads using antioxidant‐rich Syzygium caryophyllatum fruit pulp as a healthy snack

Abstract: Reverse spherification is a common technique used in molecular gastronomy to produce innovative products with an improved texture by shaping a liquid into an edible semisolid sphere that gives a burst in the mouth sensation. In this study, liquid-core hydrogel beads (LHBs) were prepared using Syzygium caryophyllatum fruit pulp adapting reverse-phase molecular gastronomy as a minimal processing technique to promote it as a healthy snack. Three types of hydrogel beads were formulated while considering the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Also, the ionic gelling crosslinking reaction stops as soon as the beads are removed from the bathing solution. Thus, the liquid core of popping boba is conducive to loading with functional ingredients, 8,9 like HA, yielding hyaluronic acid liquid‐core hydrogel beads (HA‐LHB). Some studies have reported the addition of HA into calcium alginate system to act as an thickening agent to improve the rheological properties, 10 a protective material to enhance survival of functional ingredients 3,11 or a specific binding material to deliver and transport drugs 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, the ionic gelling crosslinking reaction stops as soon as the beads are removed from the bathing solution. Thus, the liquid core of popping boba is conducive to loading with functional ingredients, 8,9 like HA, yielding hyaluronic acid liquid‐core hydrogel beads (HA‐LHB). Some studies have reported the addition of HA into calcium alginate system to act as an thickening agent to improve the rheological properties, 10 a protective material to enhance survival of functional ingredients 3,11 or a specific binding material to deliver and transport drugs 12 .…”
Section: Introductionmentioning
confidence: 99%